Castles, Forests, and Literary Syncretism. An Analysis of Horace Walpole’s The Castle of Otranto - Marnieri, María Teresa (Revista de Lenguas Modernas, 2018)
The Castle of Otranto has been considered a turning point in eighteenth-century literature and in fiction in general. This study intends to high-light some aspects that are not generally taken into consideration, such as the historical context, the architectural descriptions and the use of landscape, which will become essential in subsequent romances and novels that belong to the Gothic genre. This article also underscores narrative techniques that marked a change in the history of prose-writing. Finally, it focuses on important works, contemporary of Horace Walpole’smasterpiece that played an important role in the long eighteenth-century.